PERANG SALIB DAN KEJAYAAN SALAHUDDIN AL-AYUBI MENGEMBALIKAN ISLAMICJERUSALEM KEPADA UMAT ISLAM (Crusades and Saladin’s Achievement in Liberating Islamicjerusalem to Muslims Ummah) - Mohd Nor, Mohd Roslan; Mohd Noor, Noor Shakila (Journal of Al-Tamaddun, 2012)
It was through the Crusades that the Christians military expeditions were able to capture Islamicjerusalem from Muslim rule, thus causing the fall of Muslim authority and rule in Islamicjerusalem in 1099AD. In 1187 however, Salah al-Din al-Ayyubi (d.1193), known as Saladdin, was able to liberate Islamicjerusalem from the hands of the Crusaders. Based on historical methods of analysis, this study investigates Saladin’s plan of liberating Islamicjerusalem. This research shows that the plan of liberation has not began with Saladdin, but traces its origin back to Nur al-Din al-Zinki (d.1174), ruler of the Syrian province of the Seljuk Empire, and that Saladdin built on earlier efforts and investment in strategic plan and preparation for liberation.